The Implementation Integrating Science and Religion in Curriculum Implementation at State Islamic University in North Sumatra - Makmur Syukri; Neliwati Neliwati; Qomaruddin Lubis (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to explore the concept of integration of science and religion based on wahdhatl ulum, explore the development of the integration of science in curriculum development, and explore the development of the integration of science and religion based on wahdhatl ulum in the implementation of the curriculum at the Faculty of Tarbiyah and Teacher Training a state Islamic university in North Sumatera. This research conducted a qualitative method with a phenomenological approach. The instruments used in this research are observation, interviews, and documentation studies. The data is analyzed using inductive and interim analysis. The results show the concept of integrating science and religion based on wahdhatul ulum in leaders’ of FITK UINSU Medan view is a concept of incorporating knowledge by obviating the dichotomy or separating between general sciences and religious sciences. Preparing the curriculum begins by forming Lecture Plans (RPS) in lecture activities. Despite of, the integration of science and religion in curriculum implementation has been carried out through the process of lectures, research, and community service; however, not all lecturers have the same perception in its understanding and implementation, so there are variations in their learning activities.